One-Stage, Limited-Resection Epilepsy Surgery for Bottom-of-Sulcus Dysplasia. (13th July 2021) - Macdonald-Laurs, Emma; Maixner, Wirginia J.; Bailey, Catherine A.; Barton, Sarah M.; Mandelstam, Simone A.; Yuan-Mou Yang, Joseph; Warren, Aaron E.L.; Kean, Michael J.; Francis, Peter; MacGregor, Duncan; D'Arcy, Colleen; Wrennall, Jacquie A.; et al.
Abstract : Objective: To determine whether 1-stage, limited corticectomy controls seizures in patients with MRI-positive, bottom-of-sulcus dysplasia (BOSD). Methods: We reviewed clinical, neuroimaging, electrocorticography (ECoG), operative, and histopathology findings in consecutively operated patients with drug-resistant focal epilepsy and MRI-positive BOSD, all of whom underwent corticectomy guided by MRI and ECoG. Results: Thirty-eight patients with a median age at surgery of 10.2 (interquartile range [IQR] 6.0–14.1) years were included. BOSDs involved eloquent cortex in 15 patients. Eighty-seven percent of patients had rhythmic spiking on preresection ECoG. Rhythmic spiking was present in 22 of 24 patients studied with combined depth and surface electrodes, being limited to the dysplastic sulcus in 7 and involving the dysplastic sulcus and gyral crown in 15. Sixty-eight percent of resections were limited to the dysplastic sulcus, leaving the gyral crown. Histopathology was focal cortical dysplasia (FCD) type IIb in 29 patients and FCDIIa in 9. Dysmorphic neurons were present in the bottom of the sulcus but not the top or the gyral crown in 17 of 22 patients. Six (16%) patients required reoperation for postoperative seizures and residual dysplasia; reoperation was not correlated with ECoG, neuroimaging, or histologic abnormalities in the gyral crown. At a median 6.3 (IQR 4.8–9.9) years of follow-up, 33 (87%) patients are seizure-free, 31 off antiseizure medication. Conclusion: BOSD can be safely and effectively resected with MRI and ECoG guidance, corticectomy potentially being limited to the dysplastic sulcus, without need for intracranial EEG monitoring and functional mapping. Classification of Evidence: This study provides Class IV evidence that 1-stage, limited corticectomy for BOSD is safe and effective for control of seizures.